Incidental Adrenal Enlargement: An Overview from a Retrospective Study in a Chinese Population - Le-le Li; Wei-jun Gu; Jing-tao Dou; Guo-qing Yang; Zhao-hui Lv; Yi-ming Mu; Ju-ming Lu (International Journal of Endocrinology)
Aim. To investigate incidental adrenal enlargement clinical characteristics and functional status and analyze functional lesion risk factors. Materials and Methods. This retrospective study included 578 patients with adrenal imaging features showing enlargement. Incidental adrenal enlargement cases (78) were considered eligible. Demographics, functional diagnosis, adrenal imaging features, and concomitant diseases were analyzed. Results. The number of adrenal enlargements and proportion of incidental adrenal enlargement increased each year. Mean patient age was 50.32 years. Thirty-nine cases had unilateral enlargement on the left side and 3 on the right side; 36 had bilateral enlargement. Routine medical checkup was found to have the greatest chance (43.59%) of revealing clinical onsets leading to discovery. Biochemical and functional evaluation revealed 54 (69.23%) cases of nonfunctional lesions, 12 (15.38%) of subclinical Cushing syndrome, 6 (7.69%) of primary hyperaldosteronism, 1 (1.28%) of metastasis, and 5 (6.41%) of unknown functional status. Nodular adrenal enlargement (OR, 7.306; 95% CI, 1.727–28.667; P = 0.006) was a risk factor for functional lesions. Age and lesion location were not significant factors. Conclusion. Incidental adrenal enlargement is a frequent radiographic finding and is accompanied by diverse clinical factors that require proper evaluation and management. Nodular adrenal enlargement was a risk factor.